Web-Based Directory of ITU-UUM Partners Using Social Network Site - Jaradat, Hosam Kamil Mohammed (2010)
Directory services help people to manage their information in accurate and a secure way. It provides a foundation for modern enterprise information. Directories control names, addresses, and routes for e-mails, phones and other data. ITU-UUM center is the heart for all rural ICT development initiatives across Asia Pacific region. The center faces a problem with managing and using its partners' information, because they use a manual system to save them. This study has focused on the development of web-based directory system of ITU-UUM partners using social network technology, to help ITU-UUM staff and their partners to manage, search, and contact each others in smooth and easy way. As a result of testing the developed Web-based Directory by the staff of ITU-UUM, the results showed that the users found the application very usehl and helpful.